Probing the Nexus Effect of CO2 Emissions, Fossil Fuels, Energy Imports and Economic Growth on Renewable Energy Consumption in OIC Member Countries in Southeast Asia: Evidence from Panel Data Estimations - Olii, Rahmat (West Science Nature and Technology, 2024)
In recent years, the role of renewable energy sources has increased in the amount of energy consumed worldwide. Much remains unknown about the components that influence renewable energy consumption. This article addresses this issue for the Southeast Asian countries that are members of the Organization of Islamic Cooperation (OIC): Indonesia, Malaysia and Brunei Darussalam. Besides having major energy resources, the region is well suited for renewable energy development as it can measure the effects of carbon dioxide emissions, fossil fuels, energy imports, and economic growth. In this study, we found that there is no statistically significant difference in renewable energy consumption in previous years; economic growth and concurrent increases in carbon dioxide and fossil fuel emissions do not have a positive impact on renewable energy use in the OIC region of Southeast Asia; and the impact of energy imports has a significant impact on the consumption of renewable energy. In addition, how the findings of this study impact policy is discussed.